2006
DOI: 10.1055/s-2005-872950
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous Cystadenocarcinoma - An Extremely Rare Tumor in a Young Patient

Abstract: We report on an extremely rare case of pulmonary mucinous cystadenocarcinoma. A 29-year-old male patient was admitted because of progressive enlargement of a right lower lobe mass over a period of 10 years. Right lower lobectomy was performed after a malignant mucinous cystadenocarcinoma was diagnosed by intraoperative frozen section. PET and CT scans did not detect metastatic disease. This case is the youngest patient reported so far with a malignant pulmonary mucinous cystadenocarcinoma and highlights the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…According to Iwasaki et al (5), 20 cases of PMC had been reported so far, in patients ranging from 29 to 75 years (median, 64 years) of age, with no patient gender difference (6). The majority of patients were asymptomatic and the lesions were discovered incidentally, but some presented with non-specific respiratory symptoms including cough, chest pain, dyspnea, and bloody sputum (5, 7, 8). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Iwasaki et al (5), 20 cases of PMC had been reported so far, in patients ranging from 29 to 75 years (median, 64 years) of age, with no patient gender difference (6). The majority of patients were asymptomatic and the lesions were discovered incidentally, but some presented with non-specific respiratory symptoms including cough, chest pain, dyspnea, and bloody sputum (5, 7, 8). …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a formal anatomic lobectomy for early stage tumors is probably the correct surgical approach as mentioned by Mann et al (19). The role of adjuvant therapy chemotherapy or radiotherapy is not established (7), and given the unclear natural history of PMC, careful long-term follow-up study is probably needed.…”
Section: Discussionmentioning
confidence: 99%
“…5 We performed FDG-PET/CT and found intense uptake of FDG in the solid areas of invasive carcinoma foci; this fi nding was similar to that described in another case. 6 FDG-PET and enhanced CT might prove helpful in the preoperative diagnosis of PMC.…”
Section: Discussionmentioning
confidence: 99%
“…4 We screened the English literature based on the PubMed database and found that 19 cases of PMC had been reported so far, although some controversy exists over the number of PMC cases except that of borderline-malignant cases. [3][4][5][6][7][8][9][10] The characteristics of PMC cases including ours are summarized as follows. There were 11 men and 9 women who ranged in age from 29 to 75 years (median 64 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation